The effects of low-fat dairy products fortified with 1500 IU vitamin D3 on serum liver function biomarkers in adults with abdominal obesity: a randomized controlled trial - Payam Sharifan; Susan Darroudi; Mahdi Rafiee; Kiarash Roustai Geraylow; Romina Hemmati; Mohammad Rashidmayvan; Mohamad Safarian; Saeid Eslami; Hassan Vatanparast; Reza Zare-Feizabadi; Maryam Mohammadi-Bjgiran; Hamideh Ghazizadeh; et al. (BMC, 2023)
Abstract Introduction Vitamin D deficiency has been reported to affect liver function biomarkers. This study was aimed to investigate the effect of consuming vitamin D fortified low-fat dairy products on liver function tests in adults with abdominal obesity. Methods This total blinded randomized controlled trial was undertaken on otherwise healthy abdominally obese adults living in Mashhad, Iran. Milk and yogurt were fortified with 1500 IU vitamin D3 nano-capsules. Participants were randomized to receive fortified milk (n = 73), plain milk (n = 73), fortified yogurt (n = 69), and plain yogurt (n = 74) for 10 weeks. Blood samples were taken at baseline and at the end of the study to assess serum levels of vitamin D, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase (ALP), and Gamma glutamyl transferase. Results A total of 289 participants completed the study (54% female). The groups were homogenous in terms of age, sex, weight, energy intake, and physical activity level (p-value > 0.05). After the trial, vitamin D serum levels were significantly increased in both groups receiving fortified products (both p < 0.001). There was a significant time*group effect only in serum ALP (p < 0.001). Conclusion Consumption of dairy products fortified by 1500 IU vitamin D3 might have detrimental effects on serum levels of some liver enzymes in individuals with abdominal obesity. Further studies needed to determine these effects and underlying mechanisms. Trial registration: IRCT20101130005280N27 .